2020
DOI: 10.5505/ejm.2020.98698
|View full text |Cite
|
Sign up to set email alerts
|

Could Bladder wall elastography be used as an indicator for the diagnosys of bladder outlet obstruction by Benign Prostate Hyperplasia?

Abstract: Benign prostatic hyperplasia (BPH) is one of the most common causes of bladder outlet obstruction in me n. In this study we aimed to evaluate the elasticity of the bladder by Acoustic Radiation Force Impulse (ARFI) elastography in BPH patients. Fifty benign prostate patients were included in the study. After evaluation of patients in the outpatient clinic. A RFI elastography was performed with full bladder. Elastography was performed separately on the anterior, right and left walls of the bladder. Then the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many different pathologic processes of various diseases can alter the bladder wall structure and result in elasticity changes. Several studies have reported bladder wall evaluations by SWE 28–30 . Eryılmaz et al 29 and McDonald and Kenney 31 reported that the elastographic values of the bladder wall in patients with benign prostate hyperplasia were correlated with the prostate gland volume and uroflowmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different pathologic processes of various diseases can alter the bladder wall structure and result in elasticity changes. Several studies have reported bladder wall evaluations by SWE 28–30 . Eryılmaz et al 29 and McDonald and Kenney 31 reported that the elastographic values of the bladder wall in patients with benign prostate hyperplasia were correlated with the prostate gland volume and uroflowmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Eryılmaz et al 29 and McDonald and Kenney 31 reported that the elastographic values of the bladder wall in patients with benign prostate hyperplasia were correlated with the prostate gland volume and uroflowmetry. In these studies, it was determined that bladder wall elastographic values could be used as indicators of bladder outlet obstruction 29,31 . It was stated that 2D SWE is a useful, sensitive technique for detecting changes in the elasticity of the bladder wall and can be used to detect early fibrotic changes in patients with bladder disorders 23 .…”
Section: Discussionmentioning
confidence: 99%